1962
DOI: 10.4039/ent94337-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Host Tree on Abundance of Itoplectis conquisitor (Say) (Hymenoptera: Ichneumonidae), a Polyphagous Parasite of the European Pine Shoot Moth, Rhyacionia buoliana (Schiff.) (Lepidoptera: Olethreutidae)

Abstract: The larvae of the European pine shoot moth, Rhyacionia buoliana (Schiff.), feed on several species of hard pines, of which the most economically important are red pine, Pinus resinosa Ait., and Scots pine, Pinus sylvestris L. Approximately one hundred million trees of each species mere planted in southern Ontario since 1905, most of them since 1925. Many pure and mixed stands are now infested by R. buoliana which has no apparent preference for either host tree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 4 publications
1
32
0
1
Order By: Relevance
“…Later, Thorpe and Caudle (1938) reported that mature adult PimpZa rufiaoZZis Grav. were attracted to the odor of Pinus oil, and Arthur (1962) role of the host's food (plant) in influencing or attracting the parasitoid have been carried out (Camors and Payne 1971, Nishida 1956, Read et al 1970, Rice 1969, Streams et al 1968and Shahjahan 1974. The results of these studies demonstrate that many parasitoids do orient to factors from the host's food.…”
Section: Habitat Locationmentioning
confidence: 74%
“…Later, Thorpe and Caudle (1938) reported that mature adult PimpZa rufiaoZZis Grav. were attracted to the odor of Pinus oil, and Arthur (1962) role of the host's food (plant) in influencing or attracting the parasitoid have been carried out (Camors and Payne 1971, Nishida 1956, Read et al 1970, Rice 1969, Streams et al 1968and Shahjahan 1974. The results of these studies demonstrate that many parasitoids do orient to factors from the host's food.…”
Section: Habitat Locationmentioning
confidence: 74%
“…In numerous studies since (e.g., Taylor, 1932;Zwölfer and Kraus, 1957;Salt, 1958;Harrington and Barbosa, 1978), predators and parasitoids were found more on one plant species than another. That plant volatiles may be responsible for such differential attractiveness was apparent from studies by, among others, Monteith (1955), Arthur (1962), Flint et al (1979), and Elzen et al (1984). These studies considered the importance of the plant only at the level of habitat locations, as defined by Vinson (1981).…”
Section: The Role Of Plant Volatiles As Prey and Host Location Cuesmentioning
confidence: 99%
“…Olfactory responses to the host plant are common and parasites may show preferences between species. For instance, Itoptectis conquisitor (Hymenoptera: Ichneumonidae) is attracted to the odour of Scots pine (Pinus sylvestris) more than that of the Red pine (P. resinosa) so that the former is more heavily parasitised (Arthur 1962). Parasitism also may be influenced by physical attributes of the plant, such as surface texture in the case of Trichogramma (Flanders 1937).…”
Section: Introductionmentioning
confidence: 98%
“…Hosts in or on differing parts of the same plant may vary in vulnerability. Females of I. conquisitor are unable to parasitise pupae in buds protected by needles, and parasitism was higher in small than in large buds (Arthur 1962). Carnegie (1980) considered the growth habits of host plants to be a factor causing the low levels of parasitism by Ootetrartichus beatus (Hymenoptera: Eulophidae) and Oligosita numiciae (Hymenoptera: Trichogrammatidae) in sugarcane compared to other host plants.…”
Section: Introductionmentioning
confidence: 99%